2016
DOI: 10.1080/09540261.2016.1202812
|View full text |Cite
|
Sign up to set email alerts
|

Sport psychiatry and psychotherapeutic intervention, circa 2016

Abstract: The focus of this paper is to provide an update on the use of psychotherapy as a treatment in sport psychiatry, and the use of this approach to address common psychiatric issues encountered with this population. Specifically, family therapy, individual therapy, and group psychotherapy prescribed alone, or in combination with medication, will be examined as methods to manage issues/disorders often associated with athletes. These include obsessive-compulsive rituals and perfectionism, and aggressive and risky be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 64 publications
2
50
1
Order By: Relevance
“…This may be largely due to a binge pattern of consumption during non-competitive or vacation periods 10. Cannabis is also used in athletic populations and is associated with factors such as high sensation-seeking tendencies and overestimating the normative use of the substance 8. Seitz et al found that athletes are more likely to use cannabis recreationally compared with non-athletes 11.…”
Section: Mental Health Symptoms and Disorders As A Target For Psychotmentioning
confidence: 99%
See 4 more Smart Citations
“…This may be largely due to a binge pattern of consumption during non-competitive or vacation periods 10. Cannabis is also used in athletic populations and is associated with factors such as high sensation-seeking tendencies and overestimating the normative use of the substance 8. Seitz et al found that athletes are more likely to use cannabis recreationally compared with non-athletes 11.…”
Section: Mental Health Symptoms and Disorders As A Target For Psychotmentioning
confidence: 99%
“…Moreover, elite athletes have sport-specific medication considerations, for example, antidoping regulations and the desire for avoidance of side effects that could negatively impact athletic performance 8. Some of the side effects of particular relevance and concern for elite athlete include sedation, weight gain and tremor 8.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations